Preneoplastic liver colonization by 11p15.5 altered mosaic cells in young children with hepatoblastoma - Pilet, Jill; Hirsch, Theo Z.; Gupta, Barkha; Roehrig, Amélie; Morcrette, Guillaume; Pire, Aurore; Letouzé, Eric; Fresneau, Brice; Taque, Sophie; Brugières, Laurence; Branchereau, Sophie; Chardot, Christophe; et al. (Nature communications, 2023)
Pediatric liver tumors are very rare tumors with the most common diagnosis being hepatoblastoma. While hepatoblastomas are predominantly sporadic, around 15% of cases develop as part of predisposition syndromes such as Beckwith-Wiedemann (11p15.5 locus altered). Here, we identify mosaic genetic alterations of 11p15.5 locus in the liver of hepatoblastoma patients without a clinical diagnosis of Beckwith-Wiedemann syndrome. We do not retrieve these alterations in children with other types of pediatric liver tumors. We show that mosaic 11p15.5 alterations in liver FFPE sections of hepatoblastoma patients display IGF2 overexpression and H19 downregulation together with an alteration of the liver zonation. Moreover, mosaic livers’ microenvironment is enriched in extracellular matrix and angiogenesis. Spatial transcriptomics and single-nucleus RNAseq analyses identify a 60-gene signature in 11p15.5 altered hepatocytes. These data provide insights for 11p15.5 mosaicism detection and its functional consequences during the early steps of carcinogenesis. Paediatric liver cancer is rare, and often associated with a predisposition syndrome. Here, the authors show that 11p15.5 mosaic alteration in the liver is a pre-neoplastic lesion associated with hepatoblastoma, and spatial transcriptomics together with single-nucleus RNAseq identify a an altered zonation in the liver of these patients.